2015
DOI: 10.1002/jsfa.7129
|View full text |Cite
|
Sign up to set email alerts
|

Posidonia oceanica banquettes as a substitute for straw in dairy goat rations: metabolic and productive effects

Abstract: Goats can be fed P oceanica at levels of up to 450 g day(-1) without detrimental effects on milk production and health, therefore P. oceanica can be a substitute for barley straw in the nutrition of goats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
4
10
0
Order By: Relevance
“…As for Ca, P and Mg concentrations, and comparing them with those found in traditional forage sources [11], PO was richer in calcium and phosphorus but poor in magnesium. For goats, supplementation with PO showed that this animal was able to consume daily up to 450g/day without any detrimental effect at the productive level [12]. While for Merino sheep the optimal intake the ideal proportion to supplement was between 75 and 150g (as a limit) of PO/day [13].…”
Section: Results Obtained With the Use Of Posidonia Oceanica Residues On Small Ruminantsmentioning
confidence: 99%
“…As for Ca, P and Mg concentrations, and comparing them with those found in traditional forage sources [11], PO was richer in calcium and phosphorus but poor in magnesium. For goats, supplementation with PO showed that this animal was able to consume daily up to 450g/day without any detrimental effect at the productive level [12]. While for Merino sheep the optimal intake the ideal proportion to supplement was between 75 and 150g (as a limit) of PO/day [13].…”
Section: Results Obtained With the Use Of Posidonia Oceanica Residues On Small Ruminantsmentioning
confidence: 99%
“…The collection and management of the dried marine plant residues that were used as feedstuff was fully described in a previous report, as well as the chemical analysis of the product . Briefly, after permission for sampling from the local government, samples of banquettes of P. oceanica from six different points of the selected area were randomly collected on the same day directly from the beach above the water line, washed in a warehouse with distilled water and sun dried for 48 h. Approximately 500 g of each sample of plant material was chopped and two subsamples of 200 g each were placed in airtight plastic containers and sent to the laboratory for mineral and chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, we have demonstrated that these banquettes could play a role as a fibre source substituting for barley straw in the feed of goats, which could help to optimise production costs without detrimental effects on milk production and health …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, interest in the potential uses of these P. oceanica banquettes has increased. For instance, they have been tested as a fiber source for ruminants ( 10 , 11 ) and have been used in agriculture as an organic substrate to increase soil fertility ( 12 , 13 ). Moreover, P. oceanica has been used in traditional medicine to treat type 2 diabetes mellitus and hypertension in villagers living by the sea coast of Western Anatolia, as well as to alleviate skin diseases (i.e., acne) and leg pain caused by varicose veins ( 14 ).…”
Section: Introductionmentioning
confidence: 99%